A simple and accurate FDTD based technique to determine equivalent complex permittivity of the multi-layered human tissue in MICS band - Rahman, Mir Mohsina (H. : ĐHQGHN, 2020)
This paper proposes a methodology to determine the equivalent electrical properties of multilayered human tissue using the Finite Difference Time Domain (FDTD) method for dispersive media. In addition, the impact of fat layer thickness on the equivalent dielectric properties has also been critically analyzed. The effect of moisture content present in the skin layer has also been studied. The main advantage of the proposed method is that it can be used for any thickness and any number of layers of human tissue. The multilayer reflection and transmission coefficients of the human tissue are first calculated using the FDTD method and then the permittivity and conductivity are extracted using the Nicholson Ross Weir (NRW) Method. The results are validated analytically using the concept of transmission line analogy for plane wave propagation. The tool used is MATLAB. In this paper, a three-layered software model of the human chest for pacemaker applications has been analyzed in the Medical Implants Communication Service band (MICS). At the frequency of 403.5 MHz in the MICS band, the equivalent permittivity of 3 layered human tissue is approximately 43 and its conductivity is 0.41 s=m. Moreover, the effective permittivity, conductivity and tan delta loss decrease with the increase in fat layer thickness. These results form the basis for the development of phantom mixtures used for designing, testing and evaluation of implantable antenna and SAR measurements. The choice of using FDTD is because it is a very powerful tool for creating a numerical mixture.